A Expedição Roncador-Xingu e a tarefa de ocupar, civilizar e urbanizar o Brasil Central - Galvão, Maria Eduarda Capanema Guerra (2014)
This study intends to research the project of occupation of Central Brazil during the Estado Novo period tlu-ough the experience of Roncador-Xingu Expedition. Our interest is to investigate the policy of civilizing and urbanize the interior of the country, in search of integration between the regions The contraclictions between official projects anel claily reality are analyzed in orcler to unclerstancl the dialectic that involved the campaign anel how the ideal of progress promoted by the state agency was owned by the local populations.